SPECIALIZED (ATYPICAL) PROVISIONS NATIONAL TRANSPORT LAW - Cherneha, Vitalii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
SPECIALIZED (ATYPICAL) PROVISIONS NATIONAL TRANSPORT LAW Kyiv National Economic University named after Vadym Hetman 54/1, Beresteiskyi Avenue, 03057, Kyiv, Ukraine E-mаil: vitalii.cherneha@kneu.edu.ua Purpose: formation of a systemic vision of specialized (atypical) national transport law provisions. Research methods: analysis, synthesis, induction, deduction (thoroughly applied according to the chosen research subject); historical and legal (made it possible to reveal the system of national transport law definition-provisions through the prism of the transformation of transport legislation of Ukraine); systemic (contributed to the disclosure of the system of specialized (atypical) national transport law); prognostic (made it possible to outline the scientific prospects for the implementation of specialized (atypical) national transport law provisions); modeling (applied to form conclusions and recommendations on the subject of the selected research). Results: the author’s vision of specialized (atypical) national transport law provisions was formed, which included: national transport law goals-provisions; national transport law principles-provisions; national transport law definition-provisions; national transport law terms-provisions; operational national transport law provisions; conflict transport law provisions. It was determined that it is promising in scientific research: first, to study in detail the issue of the implementation national transport law principles-provisions; secondly, comprehensively consider the issue of improving the clarity of the national transport law definition-provisions; thirdly, to identify problems and reveal the scientific and applied potential of the national transport law terms-provisions; fourth, to reveal the issue of the implementation of conflict of conflict transport law provisions. Discussion: the national transport law goals-provisions; national transport law principles-provisions; national transport law definition-provisions; national transport law terms-provisions; operational national transport law provisions; conflict transport law provisions, included in the systematics of specialized (atypical) transport law of Ukraine provisions.